2021
DOI: 10.1111/myc.13299
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidative stress in onychomycosis: Thiol/disulphide homeostasis

Abstract: Superficial dermatophyte infections are skin diseases that are often encountered. Onychomycosis is the most frequent infectious condition of the nail unit. Dermatophytes, particularly Trichophyton rubrum, and Trichophyton mentagrophytes are the most common causes but non-dermatophyte moulds, such as Scopulariopsis brevicaulis, may also cause onychomycosis. 1 The dermatophytes are mycelial organisms generating long chains of cells and hyphae, to penetrate the stratum corneum, which is achieved by the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…In previously reported studies, a positive correlation has been observed between TPC and the DPPH assay, indicating the possible role of quantified polyphenols as free radical scavengers in the DPPH assay ( Fernandes de Oliveira et al, 2012 ). Amplified amounts of reactive oxygen species (ROS) are a major cause of oxidative stress, which is an important factor in onychomycosis pathogenesis and may cause permanent tissue and organ injury ( Zhang et al, 2021 ; Metin et al, 2021 ). Therefore, quenching of these ROS would be an important milestone to combat onychomycosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previously reported studies, a positive correlation has been observed between TPC and the DPPH assay, indicating the possible role of quantified polyphenols as free radical scavengers in the DPPH assay ( Fernandes de Oliveira et al, 2012 ). Amplified amounts of reactive oxygen species (ROS) are a major cause of oxidative stress, which is an important factor in onychomycosis pathogenesis and may cause permanent tissue and organ injury ( Zhang et al, 2021 ; Metin et al, 2021 ). Therefore, quenching of these ROS would be an important milestone to combat onychomycosis.…”
Section: Resultsmentioning
confidence: 99%
“…Onychomycosis patients revealed a thiol/disulfide homeostasis shift to oxidative stress with thiol reduction and a rise in the disulfide/native thiol, and disulfide/total thiol ratios. These outcomes may suggest the role of oxidative stress in the pathogenesis of onychomycosis ( Metin et al, 2021 ). Several types of onychomycosis entail total dystrophic onychomycosis, white superficial onychomycosis, distal and subungual onychomycosis, endonyx onychomycosis, and proximal onychomycosis ( Aggarwal et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%